Development of a Simplified, Cost Effective GC-ECD Methodology for the Sensitive Detection of Bromoform in the Troposphere - Chris Reason; Carl Palmer; Howard Waldron; Nicholas Moyo; Brett Kuyper; Raïssa Philibert; Casper Labuschagne (Sensors, 2012)
Wherever measurements have been made bromoform was found to be ubiquitous in the surface ocean in pmolar-nmolar concentrations. These measurements show concentrations in coastal regions orders of magnitude higher than in the pelagic oceans. Its atmospheric presence is primarily due to its release from algae and rapid transport to the marine boundary troposphere where it is known to participate in ozone chemistry via photochemical and catalytic pathways. Until quite recently, a limited number of studies existed (compared to other marine volatile organic compounds (VOCs)), mainly due to the analytical challenge(s) presented by the low environmental mixing ratios. In this work we detail the development of a simplified, cost effective method to detect and quantify bromoform in environmental air samples. Air samples (1.5 L) were preconcentrated onto a precooled adsorbent (Carbopack X/Carboxen 1016) trap. These samples were injected by means of rapid thermal desorption for separation and detection by GC-ECD. The system was calibrated by means of a custom-built permeation oven. A linear system response was achieved, having a detection limit of 0.73 ± 0.09 ppt. A range of environmental samples was analysed to demonstrate the ability of the technique to separate and identify bromoform from air samples. The results showed that bromoform concentrations typically averaged 24.7 ± 17.3 ppt in marine air samples, 68.5 ± 26.3 ppt in Cape Town urban air samples and 33.9 ± 40.5 ppt in simulated biomass burning plumes (SBBP).